Measuring Income Elasticity for Swiss Money Demand: What do the cantons say about financial innovation? - Andreas Fischer (Swiss National Bank, Study Center Gerzensee, 2005)
Recent time-series evidence has re-confirmed the forecasting ability of Swiss broad money. The same money demand studies and others, however, find that the income elasticity is greater than one. Such parameter estimates are difficult to reconcile with transactions demand theory. This study re-examines the estimates for income elasticity in money demand based on cross-regional evidence for Switzerland. Particular attention is given to the influence of regional financial sophistication. The cross-cantonal results find that the income elasticity lies between 0.4 and 0.6. This discrepancy between the two empirical methodologies has important consequences for the conduct of Swiss monetary policy.
Keywords: C21; E41; E50; 330; Money Demand; Cross-Regional Estimates; Regional Financial Sophistication; Einkommenselastizität der Nachfrage; Geldnachfrage; Teilstaat; Schweiz